Effectiveness of earthquake drains in mitigating liquefaction-induced settlement - Salimah A’isyah; Yelvi; Andienti Meidi; Adi Prakoso Widjojo; Rahayu Wiwik (E3S Web of Conferences)
This study evaluates the effectiveness of earthquake drains in mitigating liquefaction and examines their performance at specific frequencies in loose and medium-dense sediments. Two lab-scale shake table single-axis test series were conducted to assess this: one without mitigation and another using earthquake drains. Both models were instrumented and subjected to consistent shaking sequences at 1 Hz and 1.2 Hz frequencies. The results revealed reduced excess pore-water pressure generation around the drains due to the rapid dissipation of pore pressures during shaking. Additionally, the excess pore water pressure increased more slowly with the drains, as they allowed partial dissipation of pressure through drainage. Earthquake drains significantly reduced liquefaction potential, particularly in the middle area, where conditions shifted from liquefied to non-liquefied. Furthermore, ground treated with drains exhibited less differential settlement than untreated ground. The use of drains resulted in settlements being retrieved by 2% to 15% more than untreated conditions. The drains effectively mitigated the post-shaking liquefaction-induced settlement mechanisms. While this study demonstrates earthquake drains as a reliable and efficient measure for reducing liquefaction-induced settlement, further research is necessary to optimize their design and application.